Altered Auditory and Multisensory Temporal Processing in Autism Spectrum Disorders - Kwakye, Leslie D.; Foss-Feig, Jennifer H.; Cascio, Carissa J.; Stone, Wendy L.; Wallace, Mark T. (Frontiers in Integrative Neuroscience, 2011)
Autism spectrum disorders (ASD) are characterized by deficits in social reciprocity and communication, as well as repetitive behaviors and restricted interests. Unusual responses to sensory input and disruptions in the processing of both unisensory and multisensory stimuli have also frequently been reported. However, the specific aspects of sensory processing that are disrupted in ASD have yet to be fully elucidated. Recent published work has shown that children with ASD can integrate low-level audiovisual stimuli, but do so over an extended range of time when compared with typically-developing (TD) children. However, the possible contributions of altered unisensory temporal processes to the demonstrated changes in multisensory function are yet unknown. In the current study, unisensory temporal acuity was measured by determining individual thresholds on visual and auditory temporal order judgment (TOJ) tasks, and multisensory temporal function was assessed through a cross-modal version of the TOJ task. Whereas no differences in thresholds for the visual TOJ task were seen between children with ASD and TD, thresholds were higher in ASD on the auditory TOJ task, providing preliminary evidence for impairment in auditory temporal processing. On the multisensory TOJ task, children with ASD showed performance improvements over a wider range of temporal intervals than TD children, reinforcing prior work showing an extended temporal window of multisensory integration in ASD. These findings contribute to a better understanding of basic sensory processing differences, which may be critical for understanding more complex social and cognitive deficits in ASD, and ultimately may contribute to more effective diagnostic and interventional strategies.